If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5y + -1)(23y + -1) = 0 Reorder the terms: (-1 + 5y)(23y + -1) = 0 Reorder the terms: (-1 + 5y)(-1 + 23y) = 0 Multiply (-1 + 5y) * (-1 + 23y) (-1(-1 + 23y) + 5y * (-1 + 23y)) = 0 ((-1 * -1 + 23y * -1) + 5y * (-1 + 23y)) = 0 ((1 + -23y) + 5y * (-1 + 23y)) = 0 (1 + -23y + (-1 * 5y + 23y * 5y)) = 0 (1 + -23y + (-5y + 115y2)) = 0 Combine like terms: -23y + -5y = -28y (1 + -28y + 115y2) = 0 Solving 1 + -28y + 115y2 = 0 Solving for variable 'y'. Factor a trinomial. (1 + -23y)(1 + -5y) = 0Subproblem 1
Set the factor '(1 + -23y)' equal to zero and attempt to solve: Simplifying 1 + -23y = 0 Solving 1 + -23y = 0 Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -23y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -23y = 0 + -1 -23y = 0 + -1 Combine like terms: 0 + -1 = -1 -23y = -1 Divide each side by '-23'. y = 0.04347826087 Simplifying y = 0.04347826087Subproblem 2
Set the factor '(1 + -5y)' equal to zero and attempt to solve: Simplifying 1 + -5y = 0 Solving 1 + -5y = 0 Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -5y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -5y = 0 + -1 -5y = 0 + -1 Combine like terms: 0 + -1 = -1 -5y = -1 Divide each side by '-5'. y = 0.2 Simplifying y = 0.2Solution
y = {0.04347826087, 0.2}
| 5x^2=27 | | x^2+3x^2=x^2 | | -11x+9=-12+13 | | 6x-8=3x | | 1x-9= | | 4x-y=-10 | | t(t-2)-3t(t-2)=0 | | t(t-2)-3t(t-3)=0 | | 6(-x+4)=9 | | -2(5y+1)=4(y+6)-2 | | h=-16t^2+68t | | 5y+5=2y+10 | | 64=2(5x+2)+(3x-2) | | 2a^2-81=0 | | 1x+3x+-18x=0 | | 5x=2-2x | | x-3x+-18x=0 | | -4x^2+3x=1 | | 3(h)+6=2(h)-14 | | 3(-20)+6=2(-20)-14 | | 3x-2y+5z+au=0 | | -4x-5x=18 | | 6n^2=15+12n | | 2-4(-6)-7=3+2(-6)+4 | | 12w-5=19+6w | | 4m^2-57=7m | | 10x^2+9=379 | | -2x^2+2=3x | | 11x=8x-15-6x | | 3p^2+6=216 | | 8y-7=y | | -100=109r+118 |